The Discovery of a Low-energy Excess in Cosmic-Ray Iron: Evidence of the Past Supernova Activity in the Local Bubble - Boschini, M. J.; Della Torre, S.; Gervasi, M.; Grandi, D.; Jóhannesson, G.; La Vacca, G.; Masi, N.; Moskalenko, I. V.; Pensotti, S.; Porter, T. A.; Quadrani, L.; Rancoita, P. G.; et al. (The Astrophysical journal, 2021)
Since its launch, the Alpha Magnetic Spectrometer—02 (AMS-02) has delivered outstanding quality measurements of the spectra of cosmic-ray (CR) species ( , e ± , and nuclei, 1 H– 8 O, 10 Ne, 12 Mg, 14 Si) which resulted in a number of breakthroughs. One of the latest long-awaited surprises is the spectrum of 26 Fe just published by AMS-02. Because of the large fragmentation cross section and large ionization energy losses, most of CR iron at low energies is local and may harbor some features associated with relatively recent supernova (SN) activity in the solar neighborhood. Our analysis of the new AMS-02 results, together with Voyager 1 and ACE-CRIS data, reveals an unexpected bump in the iron spectrum and in the Fe/He, Fe/O, and Fe/Si ratios at 1–2 GV, while a similar feature in the spectra of He, O, and Si and in their ratios is absent, hinting at a local source of low-energy CRs. The found excess extends the recent discoveries of radioactive 60 Fe deposits in terrestrial and lunar samples and in CRs. We provide an updated local interstellar spectrum (LIS) of iron in the energy range from 1 MeV nucleon −1 to ∼10 TeV nucleon −1 . Our calculations employ the GalProp – HelMod framework, which has proved to be a reliable tool in deriving the LIS of CR , e − , and nuclei Z ≤ 28.